Letter - Peck, H.
034-0091-001 To General Secretary Sir Walter Citrine K.B.E. p.c. ack 21.11.38. Dear Sir I wish to express my indignation at the long delay in allowing the International Brigade to return home. I demand that the T.U.C. protest to the proper quarters & do all in their power to remove the cause of delay, so that our fellow member & sons can return to there Towns & Villages. Yours sincerely H. Peck A.S.W. 21 Latchmere Lane Kingston upon Thames 292/946/34/91